Ratiometric pathlength calibration of integrating sphere-based absorption cells - Bergin, Sarah; Hodgkinson, Jane; Francis, Daniel; Tatam, Ralph P. (Optical Society of America, 2020)
Chemical sensors based on optical absorption require accurate knowledge of the optical pathlength of the sample cell. Integrating spheres offer increased pathlengths compared to single pass cells combined with tolerance to misalignment, making them attractive for use in challenging environments subject to vibration. However, the equivalent optical pathlength can be degraded by dirt and / or condensation on the inner surface of the sphere. We present a new scheme for in-situ calibration that uses a ratiometric two-beam approach. Results are presented for an integrating sphere used in the measurement of methane by tunable diode laser spectroscopy (TDLS) at 1651nm. Reduced sphere reflectivity was simulated by applying small areas of black tape on the inner surface. At methane concentrations of 1500ppm and 3125 ppm, for areas of contamination up to 2.3% of the sphere wall, the technique reduced the error from over 50% to within ±4%. At a concentration of 6250 ppm and the most severe fouling corresponding to 2.9% wall coverage, the technique reduced the error from 55-65% to within ±11%